PENGGUNAAN GRAMATIKA DALAM WACANA POLITIK: STUDI REPRESENTASI BAHASA SEBAGAI SISTEM MAKNA SOSIAL DAN POLITIK - Santoso, Anang (Diksi, 2008)
The grammar of the Indonesian language is greatly made use of inpolitical discourse and especially after the era of the Old Order. Via grammaticalforms, the political elite fights for its power and ideology, both explicitly andimplicitly, causing an unbalanced political communication. A research study thisarticle is about was conducted to (1) describe and interpret the utilization ofgrammaticality in political discourse and (2) clarify why certain grammaticalforms are paid special attention while others are not.The study applied a critical qualitative approach with a "critical discourseanalysis" design from Fairclough (1989: 1995). In this perspective, no textproduced by the political elite is neutral from political interest. Discourse is asocial construction and results from social-historical and political conditions.There is no discourse which is a social vacuum. Discourse is a social creationreflecting the interests of certain social groups.The research results indicate that (1) each group of the Indonesianpolitical elite uses transitivity with material meaning, agent nominalization, thepassive voice, and the negative form to show its power and hide its ideologicalposition, (2) each assumes the role of information provider, shows its authority inthe presence of the other groups and the Indonesian society, and asserts its powerby choosing to use the personal pronouns we and I, (3) it makes considerable use ofmodality expressing authority, and (4) there are institutional and cultural processesexplaining why certain grammatical forms are paid special attention while othersare not.Keywords: grammaticality, political discourse